Sensory Shelf life of "Aji de Gallina" packaged using accelerated survival statistics - Silva, Diego (2016)
This present research aimed to determine the sensory shelf life of "Aji de Gallina" packed in glass jars by statistical survival with accelerated testing. Were prepared Samples, which were stored at 30, 40 and 50 °C for 47 days, for which 50 untrained panelists (consumers) were recruited. The survival statistical model’s parameters were 3.9372 μ ± 0.08, 0.06 ± 0.1593, 3.6905 ± 0.05 and 0.1512 ± parameters σ were 0.04, 0.02 ± 3.6003, 0.0692 ± 0.02; accruing to storage temperatures of 30, 40 and 50 °C, respectively, with an activation energy value of 11.63 ± 3.234 kJ / mol. Finally, it was concluded that sensory shelf life of "Aji de Gallina" packed in glass jars at 20 °C storage, with 50% rejection, was 53.49 ± 4.76 days.